Interlocking directorates and competition in banking - Guglielmo Barone; Fabiano Schivardi; Enrico Sette (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2022)
We study the effects on corporate loan rates of an unexpected change in the Italian legislation which forbade interlocking directorates between banks. Exploiting multiple firm-bank relationships to fully account for all unobserved heterogeneity, we find that prohibiting interlocks decreased the interest rates of previously interlocked banks by 16 basis points relative to other banks. The effect is stronger for high quality firms and for loans extended by interlocked banks with a large joint market share. Interest rates on loans from previously interlocked banks become more dispersed. Finally, firms borrowing more from previously interlocked banks expand investment, employment and sales.
Keywords: G21; G34; D34; 330; Interlocking directorates; competition; banking